PARTISIPASI PUBLIK DAN KETERBUKAAN INFORMASI DALAM PENYUSUNAN KEBIJAKAN - Ida Rahma (Jurnal Hukum Samudra Keadilan, 2019)
Public participation can be understood as activities undertaken to affect public policy formation process. Public participation is important to ensure that any policy that produced not only benefit certain people, but also a positive impact on society. The process can be performed through the stages of agenda setting, policy formulation and implementation. This paper is about to describe the transformation of society prevailing in Aceh after the peace agreement. Review of the literature of choice in this paper, which is supported by a wide range of documents related to public participation, freedom of public information, and peace building. The results of this study indicate that public participation in policy formation in Aceh have ups and downs. Post-signatories to the peace agreement, the level of public participation is very good especially in the establishment of the Law on Governing Aceh and Aceh Qanun number. Next, in 2009-2014 public participation in policy formation decreased. Furthermore, the level of public participation in policy formation is determined by freedom of public information.